(untitled) (Global Journal of Science Frontier Research, 2012)
Defatted ground nut, soybean and palm kernel cakes were stored for three months at ambient, refrigeration and display conditions. Samples were assayed for nutritive, aflatoxins and microbiological properties. Proximate parameters significantly (p